CDy14 : a novel biofilm probe targeting exopolysaccharide Psl - Kwon, Haw-Young (2020)
Detection of biofilm bacteria would be an ideal method for the physicians to diagnose chronic bacterial infections directly, but there are few imaging probes available so far. Here, we report the development of a novel biofilm detecting fluorescent probe, CDy14, through an unbiased screening of a fluorescence library and elucidated its binding partner Psl, an exopolysaccharide of the biofilm.